Understanding abiotic stress in alfalfa: physiological and molecular perspectives on salinity, drought, and heavy metal toxicity - Daud, Muhammad; Qiao, Haixia; Xu, Shouming; Hui, Xue; Adil, Muhammad; Lu, Yan (Frontiers in Plant Science, 2025)
Alfalfa (Medicago sativa L.), a vital perennial legume forage, has been widely cultivated owing to a variety of favorable characteristics, including comprehensive ecological resilience, superior nutritive value, digestibility, and nitrogen fixation capacity. The productivity traits of alfalfa, particularly its biomass yield and forage quality, are profoundly influenced by a range of abiotic stress conditions. As a common abiotic stress, drought adversely impacts growth and photosynthetic efficiency, accompanied by increased oxidative damage and stomatal closure as a mechanism to minimize water loss; meanwhile, transgenic approaches have been employed to enhance drought resilience by improving antioxidant activity and water-use efficiency. Salinity stress disturbs ionic balance, resulting in sodium (Na+) toxicity and the generation of oxidative damage; however, alfalfa cultivars exhibit salinity tolerance through mechanisms such as Na+ exclusion, K+ retention, activation of antioxidant defenses, hormonal regulation, and the upregulation of stress-responsive genes. In addition, heavy metals pose a significant challenge to alfalfa production, as they impair plant development and disrupt symbiotic nitrogen fixation, but recent studies have highlighted the potential of microbial-assisted phytoremediation in mitigating these detrimental effects. By integrating recent findings, this review highlights the intricate physiological, biochemical, and molecular mechanisms involved in alfalfa’s responses to key abiotic stressors specifically drought, salinity, and heavy metal toxicity. Breakthroughs in genetic modification, notably the development of transgenic lines exhibiting altered expression of stress-responsive genes, offer valuable potential for improving stress resilience. Future research should employ omics approaches, advanced gene-editing and de novo gene synthesis to target key regulatory elements responsible for stress adaptation.